Analysis of the Association Between Vitamin D Deficiency and Other Diagnoses of Patients by Data Mining Techniques - Kaya, Buket; Günay, Abdullah; Özüdoğru, Osman (My University, 2020)
One of the most common disorders is vitamin D deficiency. Vitamin D deficiency in individuals with avitamin D level of less than 20 ng / ml has been studied in previous studies, which is also associated withother diagnoses. The aim of this study was to investigate the association of vitamin D deficiency patientswith other diagnoses. In this respect, a data set consisting of patients whose vitamin d levels have beenmeasured in a public hospital for the last 3 years has been provided. Using this data set, the associationrule analysis of data mining techniques was performed. Apriori algorithm was preferred in the analysis.As a result of the analysis, 22 association rules were determined and interpreted.
Keywords: Tıbbi İnformatik; Bilgisayar Bilimleri; Yazılım Mühendisliği; Genel ve Dahili Tıp